2021
DOI: 10.1016/j.ultsonch.2021.105650
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and temperature-cycling retrogradation of high-amylose corn starch: Impact of sonication on its structural and retrogradation properties

Abstract: Highlights Sonication induced a partial depolymerization of starch molecules. Sonication treatment induced the appropriate structural changes for retrogradation. The degree of retrogradation degree was not affected by sonication. Retrogradation rate was greater in sonicated starch than in non-sonicated starch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This interaction impacts on the formation of perfect crystallite. Nuclei formation by amylose determines crystallization rate [17]. Long-term storage at the rumah bulat with an arid climate and the heat from the furnace during daily cooking contributes to forming starch crystal formation.…”
Section: Proximate Composition and Dietary Fibermentioning
confidence: 99%
“…This interaction impacts on the formation of perfect crystallite. Nuclei formation by amylose determines crystallization rate [17]. Long-term storage at the rumah bulat with an arid climate and the heat from the furnace during daily cooking contributes to forming starch crystal formation.…”
Section: Proximate Composition and Dietary Fibermentioning
confidence: 99%
“…Relatively more amylose short-to-intermediate chains or longer amylopectin intermediate chains can further increase the rate and extent of crystallization of rice amylopectin molecules [ 65 ]. This is supported by a study on corn starch, which showed that shortened amylose molecules subjected to sonication (noting that sonication can cause molecular degradation) became more readily leached out from starch granules during gelatinization; these leached molecules were postulated to align into nuclei and thus to accelerate the retrogradation process [ 79 ].…”
Section: Starch Order-disorder Structural Changes During Conventional...mentioning
confidence: 88%
“…Low viscosity indicates higher resistance to retrogradation, and the addition of mangrove fruit enhances the retrogradation. Retrogradation is a step wherein the gelatinized starch forms an ordered configuration by cooling to increase the crystallinity to create rigidness and firmness of the product [ 133 , 134 ]. The addition of mangrove can be used for a product with a high final viscosity, such as pudding.…”
Section: The Mangrove Fruit In the Intermediary Stage Of Processed Foodmentioning
confidence: 99%